﻿A DOUBLE SAMPLING PLAN FOR THE ZERO-INFLATED POISSON DISTRIBUTION IN THE FOOD INDUSTRY - AVIANDRI SUHARTO ﻿23415051 , ﻿RIZKI
﻿Implementing appropriate sampling plan is an important task to protect consumers from pathogenic microorganisms in the food industry. In this study, we develop a double sampling plan (DSP) for the zero-inflated Poisson distribution as an alternative sampling plan. This research provides R-code to determine the plan parameters such as the number of sample size, the acceptance number, and the ), and the number of the sample 숵ݎ, and 숵ܿ,숵셊rejection number on the first stage ( ). 숶ܿand 숶셊size and the acceptance number on the second stage ( The DSP performs better than the single sampling plan (SSP) in terms of average sample number (ASN) and total risk with the same level quality, acceptable quality level (AQL) and lot of tolerance percent defective (LTPD). Simulated data with ) are , ߚ 숶݌, 쇙, 숵셌) and specified values ( 쇮various set of given mixing proportion ( used to illustrate the applications.